Poly-microbia biofilms are Candida albicans strain and morphology dependent - Arzmi, Mohd Hafiz; Dashper, Stuart; Reynolds, Eric; McCullough, Michael (2015)
Introduction: Oral biofilms are formed by various microorganisms such as C. albicans, Actinomyces naeslundii and Streptococcus mutans. Biofilm forming ability is one of the virulent factors of C. albicans and this may be involved oral carcinogenesis. Our objective was to assess C. albicans, A. naeslundii and S. mutans interaction in the formation of poly-microbial biofilms. Methods: Four C. albicans ATCC strains (32354, MYA-2876, 90234, and 18804), two HIV isolates (genotype-A and genotype-B), two oral cancer isolates (OC1 and OC2), A. naeslundii (NCTC 10301) and S. mutans (Ingbritt) were used in this study. To study intra-kingdom biofilm formation, 24 h culture of C. albicans, A. naeslundii and S. mutans grown in Sabauraud’s dextrose agar, blood agar and Todd-Hewitt yeast extract agar, respectively, were suspended in artificial saliva medium (ASM) or RPMI-1640 to give 106 cells mL-1, 107 cells mL-1 and 108 cells mL-1, respectively in the well of 96-well plate and incubated for 72 h at 37°C. Subsequently, biofilm was stained with crystal violet or XTT to measure biomass and metabolic activity, respectively, and the absorbance at 620nm wavelength measured. To study inter- kingdom biofilms, the same protocol was repeated, except combinations of microorganisms were inoculated in a same well. Results: Growth of C. albicans was predominantly by yeast and hyphal form when grown in ASM and RPMI-1640, respectively. Biofilm biomass of C. albicans co- cultured with A. naeslundii and/or S. mutans was C. albicans strain and morphology dependent. More often high biofilm biomass (HBB) observed in ASM-grown biofilm (43.7%), and more often high metabolic activity (HMA) was observed in RPMI- grown biofilm (65.6%).